Pemanfaatan Media Sosial TikTok dalam Mata Pelajaran Pendidikan Agama Islam untuk Meningkatkan Minat Belajar Siswa di Kelas VIII SMP Negeri 26 Padang - Riswandi, Siti Fadhila; Alfurqan, Alfurqan (TSAQOFAH, 2025)
This study aims to describe the use of the social media platform TikTok in the Islamic Religious Education (Pendidikan Agama Islam or PAI) subject to enhance the learning interest of eighth-grade students at SMP Negeri 26 Padang, as well as to identify the supporting and inhibiting factors in its implementation. The study is motivated by the low student interest in PAI due to monotonous and less interactive teaching methods. A qualitative approach was employed using a field study method, with data collected through observation, interviews, and documentation. Data were analyzed using an interactive model involving data reduction, data presentation, and conclusion drawing, with data validity ensured through triangulation of sources, techniques, and time. The findings indicate that using TikTok as a learning medium has a positive impact on increasing student interest. Teachers utilized short, visual, and communicative educational videos, drawing on both existing content and self-produced materials. Supporting factors include access to technology, student enthusiasm for the platform, and teacher creativity in delivering content. Inhibiting factors involve limited digital infrastructure, potential distractions from non-educational content, and a lack of control over irrelevant material. Therefore, the use of TikTok in PAI instruction should be structured and continuously monitored to ensure alignment with educational objectives and Islamic values.